Corporate finance : exercises - Vlachý, Jan, 1964- (Leges, 2015)
Sbírka otázek zaměřených na problematiku podnikových financí.
Anglicko-český slovník
Keywords: finance podniku -- úlohy; finanční management -- úlohy; business finance -- problems, exercises, etc; financial management -- problems, exercises, etc; učebnice; textbooks